Double concertos for violin and cello with orchestra by Johannes Brahms and Vitalyi Kyreiko: genrе and style dimentions - Yaropud, Natalya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
The relevance of the article. The Concertos for violin and cello with symphony orchestra by J. Brahms (a moll, op. 102) and V. Kyreikо (a moll, op. 65) are considered in terms of embodying the artistic pursuit of composers of different eras and national schools. Genre-stylistic features are outlined, their individual and common features are revealed, which testify to the preservation and development of the tradition of the concert genre, the reinterpretation of the Brahms concert model in a new cultural context. It is emphasized that works belong to the type of symphonized concert, in which the means of symphonic transformation of thematic material, a rich polyphonic texture, complex forms of interaction between soloists and orchestra prevail. It is noted that the methods of symphonizing the musical fabric take place in accordance with the creative attitude of each composer, whose common stylistic space fits into the paradigm of romanticism — neoromanticism. Special attention paid to the V. Kyreiko’s concerto for violine and cello with orchestra, as the first in Ukraine double concert for string instruments, which is considered from point of imitation and development of the genre of instrumental concert. Emphasized the uniqueness of the author’s concept, which is revealed in the combination of deep musical content and clear form, understanding of the expressive possibilities of the violin and cello, and the disclosure of the natural beauty of the sound of the instruments. The main objective of the article is to compare the genre-stylistic features of the double concertos for violin and cello with the orchestra by J. Brahms and V. Kyreiko and to reveal the possibilities of their modern performance interpretation. The methodology of the research methodology includes the following methods: historical, which made it possible to determine the historical framework and attribute the work of composers to a certain era and style; genre-style analysis, which made it possible to reveal the stylistic features of musical expressiveness in the specified works of the composers; comparative analysis, thanks to which it became possible to compare intonation genre-style complexes in the work of composers; performance analysis, with the help of which the artistic and performance specifics of the double concerto for violin and cello with orchestra are highlighted in the aspect of updating the genre tradition of the 19th - second half of the 20th centuries. Results and conclusions. A comparative analysis of two original in design and methods of musical implementation of concertos for violin and cello and symphony orchestra by J. Brahms and V. Kуreiko allowed us to outline the wide genre and style space of existence of these bright artistic phenomena, which extends from the romanticism of the 19th century to the neo-romanticism of the 20th century, demonstrates the durability genre tradition, reveals the common features and individual differences of these works. Despite the different national and cultural context, both works embody the symphonic scale of the development of musical thought, they are marked by the breadth and ambiguity of lyrical and dramatic images. The thematic layer of the concerts is distinguished by its imaginative breadth: an epic story, elegiac romantic-song episodes, a multifaceted lyricaldramatic sphere, genre-dance finales with different emotional moods. The principle of thematic development is built on the basis of complementarity, contrasting juxtapositions of theme-images, avoidance of sharp clashes, associatively reminiscent of romantic poetic dramatic concepts. The double concertos for violin and cello by J. Brahms and V. Kуreiko demonstrate perfect skill in the presentation of each of the soloists, the construction of ensemble dialogues, and the interaction of the soloists with the orchestra. As a general trend, we state that both concerts continue the tradition of symphonizing the genre. Reviews of concerts performed by leading Ukrainian musicians of different generations (O. Horokhov — V. Chervov, B. Pivnenko — K. Polyanska) provide examples of standard performance versions, the performers’ deep understanding of the composer’s concepts, their inclusion in the general cultural and historical process. Undoubtedly, they are guidelines for further revealing the artistic potential of concerts.